THE INSTITUTE OF LIVING LAW - Ehrlich, Eugen; Yatsiuk, І. Ya.; Nykyforak, M. V.; Savchuk, S. V. (Ehrlich's Journal, 2023)
The paper, published in 1911 on the pages of the Juristische Blätter, refers, firstly, to a dispute between Eugen Ehrlich and a scientific and practical priority in the aspect of the creation of an institution of applied law (in contrast to his dispute with another subject) with Geny Franсois in 1903 (Rechtsfindung und freie Rechtswissenschaft [The Free Law Finding and Free Jurisprudence]), or a dispute with Max Ernst Mayer in 1913 (Grundlegung der Soziologie des Rechts [Foundation of the Sociology of Law]), secondly, about the critique of the program of the Institute of Applied Law, thirdly, about the task of the Institute of living law of Ehrlich himself. In the first case it’s about a proposal and a plan of the professor of the Wien University (prof. Sperl) to establish the Institute of Applied Law. Ehrlich notes that, on the one hand, his own initiative to establish the Institute of Living Law and its implementation appears earlier, and on the other hand, that the institute of living law has tasks that coincide with the ones of the corresponding Sperl’s institute, and well as others that don’t, with the latter being more valuable both for science (scholarship) and practice. In general, Ehrlich denies the need to create the mentioned Institute of Sperl. This "should be the institution of the application of the established law that therefore, is exclusively enclosed in the paragraphs, not the institute of studying the real-life law that develops and which is not spelled out in paragraphs". Consequently, the Institute of Applied Law should deal only with utilitarian tasks (for example, a collection of teaching materials for conducting classes on the basis of visibility, etc.), and not scientific, related to the study of living law. In turn, the Institute of Living Law, according to the plan of Eugen Ehrlich, has a task of teaching scientific methods, encouraging students to independent mental activity. A branch of living law can be easily imagined as an integral part of the Institute of Living Law, the task of which would be to supply the Institute with materials and equipment, as well as archiving the results of the data, collected and processed by the Institute.